The Role of Bhabinkamtibmas Through Counseling to Overcome the Crime of Two-Wheeled Theft at the Ciamis Police - Nadapdap, Frans Billy (Police Studies Review, 2024)
This research was motivated by the increasing number of criminal acts of theft of two-wheeled motorized vehicles in Ciamis District. The high level of community activities in Ciamis District means that criminal acts are also high. This thesis writing uses a qualitative approach with descriptive research type. Data collection techniques using interviews, observation and document review. There are primary and secondary data sources and the theories used to analyze are role theory and management theory. The results of the research found that the role of Bhabinkamtibmas in preventing criminal acts of two-wheeled theft was carried out through coaching provided to Bhabinkamtibmas. Meanwhile, the efforts made by Bhabinkamtibmas are through door to door outreach activities. There are factors that influence Bhabinkamtibmas in carrying out its duties, namely internal factors consisting of human resource factors, facilities and infrastructure factors, and budget factors, while external factors come from the community itself. Based on the discussion of this research, the author provides suggestions to the leadership to carry out analysis and evaluation of Bhabinkamtibmas personnel and have standardization for assessing Bhabinkamtibmas members, emphasizing providing material to the public regarding theft of two-wheeled motorized vehicles, improving the advice and infrastructure owned by the Ciamis Police, as well as providing rewards and punishments to Bhabinkamtibmas members to motivate them in their work.